Tinjauan Faktor Penyebab Ketidaklengkapan Pengisian Formulir Informed Consent di RSUD Dr. H. Moch Ansari Saleh Banjarmasin - Ningsih, Eka Rahma; S, Ravenalla; Lestiani, Novia; anhar, Aus; Imam, Mohammad (Universitas Respati Yogyakarta, 2021)
ABSTRACTCompleteness of filling in the informed consent sheet in the medical record file is very important because it will affect the legal aspects of the medical record and the quality of the medical record so that in filling in the completeness of the data in the informed consent sheet it is necessary to carry out maximum implementation .. RSUD dr. H. Moch. Ansari Saleh Banjarmasin in 2012 showed that the level of incompleteness in the approval of medical treatment in the hospital room (surgery) was below 90% with the May period with a percentage of 46.7%. June with a percentage of 31.7% and 36.6%. The research objective was to determine the factors causing the incompleteness of filling out the informed consent form at RSUD DR. H. Moch Ansari Saleh Banjarmasin. Qualitative research method is descriptive survey. Respondents were 1 gynecologist, 1 head of medical records and 1 reporting officer for emdis records. Collecting data using interviews and observation of informed consent sheets. The results of the study identified the incomplete informed consent form by examining the patient identification component, the information content component, and the patient identification component. As well as identifying the availability of standard operating procedures (SOP) for approval of medical action. Based on the research results, it can be concluded that the informed consent form did not meet the national and standard filling standards in RSUDdr. H. Moch Ansari Saleh Banjarmasin because for the standard of completeness, the informed consent must be 100% complete. The filling of informed consent was not complete 100% in two components, namely the information content component (18.2% complete and 81.7% incomplete) and the patient's authentication component (90.7% completeness and 9.3% incomplete). The factor of incompleteness in filling out the informed consent based on the results of the research carried out was because the responsible doctor did not fill in the informed consent form again, both the content component and the patient authentication component) because he was busy providing services to other patients and there was no training related to filling the informed consent form.Â Keyword : informed consent, Factors Causing Incompleteness